2019
DOI: 10.1007/s40429-019-00279-7
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Co-occurrence of Gaming Disorder and Other Potentially Addictive Behaviors

Abstract: Purpose of Review The playing of videogames has become an everyday occurrence among many adolescents and emerging adults. However, gaming can be problematic and potentially addictive and problematic gamers can experience co-occurring behavioral or substance use-related problems. The aims of the present review were to (i) determine the co-occurrence of potentially addictive behaviors with problematic and disordered gaming, and (ii) elucidate the potential risk factors in the development and maintenance of co-oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 140 publications
(198 reference statements)
7
93
0
1
Order By: Relevance
“…As for the personality traits examined, IGD and consciousness were inversely correlated. This is a finding that echoes those reported in the fields of internet addiction, gambling disorder, and substance addictions [ 22 , 74 ], all of which are related to the IGD construct [ 75 ]. In contrast to other studies [ 13 ], the correlation between IGD and neuroticism was weak.…”
Section: Discussionsupporting
confidence: 78%
“…As for the personality traits examined, IGD and consciousness were inversely correlated. This is a finding that echoes those reported in the fields of internet addiction, gambling disorder, and substance addictions [ 22 , 74 ], all of which are related to the IGD construct [ 75 ]. In contrast to other studies [ 13 ], the correlation between IGD and neuroticism was weak.…”
Section: Discussionsupporting
confidence: 78%
“…The reason for the low rate of treatment seeking may be due to structural issues such as the homogeneity of available treatments (intensive and face-to-face). In addition, individual factors related to GD may delay or inhibit treatment seeking, such as low insight, procrastination, impulsivity, and shyness or introversion (43)(44)(45)(46). Another possibility is that some individuals with gaming-related problems may initially seek out information, social support and assistance from less formal, convenient sources, such as online support groups (47).…”
Section: Introductionmentioning
confidence: 99%
“…Another important consideration for interventions is the complex nature of GD cases. Given high rates of co-morbidity and GD (e.g., depression, anxiety, substance use and gambling disorder) it may be that people with GD attend other services for more acute issues and therefore do not report seeking help for GD (46). Lau et al (48) for example, examined the records of 5820 clinically referred youth in the Canadian mental health system and reported that moderate to severe problematic gaming was reported by 13% of the sample; however, most of the sample had been referred for issues including threat or danger to self or others, or other psychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the low rate of treatment seeking may be due to structural issues such as the homogeneity of available treatments (intensive and face-to-face). In addition, individual factors related to GD may delay or inhibit treatment seeking, such as low insight, procrastination, impulsivity, and shyness or introversion (32)(33)(34)(35). Another possibility is that some individuals with gaming-related problems may initially seek out information, social support and assistance from less formal, convenient sources, such as online support groups (36).…”
Section: Introductionmentioning
confidence: 99%
“…Another important consideration for interventions is the complex nature of GD cases. Given high rates of co-morbidity and GD (e.g., depression, anxiety, substance use and gambling disorder) it may be that people with GD attend other services for more acute issues and therefore do not report seeking help for GD (35). Lau et al (37) for example, examined the records of 5820 clinically referred youth in the Canadian mental health system and reported that moderate to severe problematic gaming was reported by 13% of the sample; however, most of the sample had been referred for issues including threat or danger to self or others, or other psychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%